Raman Spectra and Calculations of the Normal Vibrations of some Organotin Compounds - El- Behairy, M.; I. Ibrahim, Aisha (Asian Journal of Chemistry, 2010)
Low frequency Raman spectra of a series of tin compounds; tetramethyl-tin Me4Sn, hexamethyldistannane Me6Sn2, bis (trimethylstannyl) dimethyl-tin (Me3Sn)2-SnMe2, tris (trimethylstannyl) organotin (Me3Sn)3 SnR (R = Me, Et, Bu, i–Bu, n-pentyl and phenyl) and tetrakis (trimethylstannyl) tin (Me3Sn)4Sn, were recorded and assigned in the region 0–600 cm–1. The normal vibrations of these compounds have been calculated and discussed in relation to the observed spectra. It was evident from the data that on going from Me8Sn3 → Me10Sn4 → Me12Sn5, the change in the vibration frequencies was very small and no shifts are observed for the C–Sn–Sn–stretching vibrations. On the other hand the symmetric and asymmetric stretching vibrations of Sn–Sn display a systematic decrease in the frequencies, which is in harmony with the calculated data. The decrease in vibration frequencies correlate well with published data of 1J(Sn–Sn) coupling constant.